Modernist Anthropology : From Fieldwork to Text - Manganaro, Marc (Book collections on Project MUSE., 1990)
Recent insights into the nature of representation and power relations have signaled an important shift in perspective on anthropology: from a fieldwork-based "science" of culture to an interpretive activity bound to the discursive and ideological process called "text-making." This collection of essays reflects the ongoing cross-fertilization between literary criticism and anthropology. Focusing on texts written or influenced by anthropologists between 1900 and 1945, the work relates current perspectives on anthropology's discursive nature to the literary period known as "Modernism.". The essays, each demonstrating anthropology's profound influence on this important cultural movement, are organized according to discourse type: from the comparativist text of Frazer, to the ethnographies of Boas, Benedict, Mead, and Hurston, and on to the surrealist experiments of the College de Sociologie. Meanwhile the book's orientation shifts from essays that approach anthropology from the vantage points of literariness and textual power to those that contemplate what bearing the junction of cultural theory and anthropology can have upon present and future social institutions. In addition to the editor, contributors include Vincent Crapanzano, Deborah Gordon, Richard Handler, Arnold Krupat, Francesco Loriggio, Michele Richman, Marty Roth, Marilyn Strathern, Robert Sullivan, John B. Vickery, and Steven Webster. Originally published in 1990. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905